The Barriers to Myocardial Infarction Patients\' Participation in Cardiac Rehabilitation Program - Ardeshir Afrasiabi-Far; Parkhideh Hosseini; Masoud Fallahi-Khoshknab; Fariideh Yaghmaei (Journal of Rehabilitation, 2008)
Objective: Cardiac rehabilitation increases quality of life, decreases recurrence, and improves physical performance and psychological status. This report aimed to examine barriers to patients' participation in cardiac rehabilitation program.